2013
DOI: 10.1016/j.pbb.2012.12.026
|View full text |Cite
|
Sign up to set email alerts
|

The mu/kappa agonist nalbuphine attenuates sensitization to the behavioral effects of cocaine

Abstract: Sensitization refers to an increase in sensitivity to a drug and is believed to play a role in the etiology of substance use disorders. The purpose of the present study was to evaluate the ability of the mixed mu/kappa agonist nalbuphine to modulate sensitization to the locomotor and positive reinforcing effects of cocaine. Rats were habituated to a locomotor activity chamber and treated with saline (1.0 ml/kg, ip), cocaine (10 mg/kg, ip), or cocaine + nalbuphine (10 mg/kg, ip) every day for 10 days. Following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Activation of KOR on DA terminals inhibits DA release in the NAc, which is implicated in the dysphoria that follows drug withdrawal (Tejeda et al, 2012). These findings have generated interest in KOR antagonists or partial agonists as medications to prevent relapse in addiction (Al-Hasani et al, 2013;Butelman et al, 2012;Grosshans et al, 2015;Schlosburg et al, 2013;Smith et al, 2013a). The effects of drugs on the opioid system in the human brain have been investigated with positron emission tomography (PET) using [ 11 C]carfentanil to assess MOR and their occupancy by enkephalins.…”
Section: Box 2 Opioid Regulation Of the Mesolimbic Da Pathwaymentioning
confidence: 99%
“…Activation of KOR on DA terminals inhibits DA release in the NAc, which is implicated in the dysphoria that follows drug withdrawal (Tejeda et al, 2012). These findings have generated interest in KOR antagonists or partial agonists as medications to prevent relapse in addiction (Al-Hasani et al, 2013;Butelman et al, 2012;Grosshans et al, 2015;Schlosburg et al, 2013;Smith et al, 2013a). The effects of drugs on the opioid system in the human brain have been investigated with positron emission tomography (PET) using [ 11 C]carfentanil to assess MOR and their occupancy by enkephalins.…”
Section: Box 2 Opioid Regulation Of the Mesolimbic Da Pathwaymentioning
confidence: 99%
“…1013 Recent behavioral studies have suggested that mixed MOR and KOR activity may be useful for the treatment of addiction/dependence and cocaine abuse. 14–16 We have reported that treatment of rhesus monkeys with cyclorphan (an analog of levorphanol, Figure 1), which has mixed KOR and MOR activity, reduced cocaine self-administration and produced fewer side effects than κ-selective agonists. 17 Another analog, butorphan (Figure 1) in contrast to a partial effect with cyclorphan, exhibited full antinociception in the warm-water tail flick test in rats, 10b and was shown to be 40 times more potent in suppressing abstinence in morphine dependent monkeys.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, these compounds do not modify basal dopamine levels, a hallmark of the stimulants [21,25,30]. κ-Opioid receptor agonists attenuate stimulantinduced increases in locomotor activity in rats [21,29,46]. κ-Opioid agonists also decrease responding maintained by cocaine and reduce the reinstatement of abolished cocaine and amphetamine use in rats [24,28,31,32,38,46].…”
Section: Studies In Rodentsmentioning
confidence: 99%
“…κ-Opioid receptor agonists attenuate stimulantinduced increases in locomotor activity in rats [21,29,46]. κ-Opioid agonists also decrease responding maintained by cocaine and reduce the reinstatement of abolished cocaine and amphetamine use in rats [24,28,31,32,38,46]. In mice, these compounds reduce the enhancement of dopamine release produced by non-neurotoxic doses of methamphetamine, and also inhibit the reduction of dopamine levels produced by neurotoxic doses of this stimulant [25].…”
Section: Studies In Rodentsmentioning
confidence: 99%
See 1 more Smart Citation